2008
DOI: 10.1002/14651858.cd004725.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal fixation surgery for acute traumatic spinal cord injury

Abstract: The current evidence does not enable conclusions to be drawn about the benefits or harms of spinal fixation surgery in patients with traumatic SCI. Well-designed, prospective experimental studies with appropriately matched controls are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…There is still need for high-quality trials to examine the role of decompressive surgery in other, less obvious circumstances. 11 The final constituent of our treatment regimen was cooling. There has, over the years, been modest interest in therapeutic hypothermia for traumatic SCI, 27 with interest more recently focusing on systemic cooling.…”
Section: Discussionmentioning
confidence: 99%
“…There is still need for high-quality trials to examine the role of decompressive surgery in other, less obvious circumstances. 11 The final constituent of our treatment regimen was cooling. There has, over the years, been modest interest in therapeutic hypothermia for traumatic SCI, 27 with interest more recently focusing on systemic cooling.…”
Section: Discussionmentioning
confidence: 99%
“…[522] However, with reference to patients with “complete” deficits in particular, the need for surgery has remained even more controversial,[13] with several authors advocating nonoperative management of these patients showing outcomes either comparable or superior to patients who undergo surgical stabilization. [2] Therefore, management of these patients revolves around the prevention of complications, early rehabilitation, and re-integration into society. Hence, we aimed to compare the clinical outcomes and cost-effectiveness of surgical stabilization versus conservative management of spinal injury in patients with complete deficits, essentially from a developing country's point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating injuries usually require surgery to assess for foreign bodies and to clean the wound to prevent infection. The timing of surgery is not clearly defined and remains controversial (30). Earlier studies suggested that medical complication rates are lower in patients who undergo early surgery, which translates into earlier mobilization and reduced hospital length of stay.…”
Section: Delay In Spinal Cord Injury Diagnosis Due To Sedation E415mentioning
confidence: 99%